Macronyssus ellipticus - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus ellipticus (Kolenati, 1856) Caris ellipticus Kolenati, 1856: 16. Liponyssus ellipticus .— Hirst, 1922: 795. Ichoronyssus mohrae Vitzthum, 1932: 32 (synonymy by Radovsky, 1966). Ichoronyssus ellipticus .— Pinchuk, 1970: 82. Macronyssus ellipticus .—Fonseca, 1941: 263; Radovsky, 1966: 94; 1967: 128; Beron, 1968: 159; Haitlinger, 1978: 707; Haitlinger & Ruprecht, 1985: 616; Baker & Beccaloni, 2006: 173; Scheffler, 2010; Radovsky, 2010: 56. Type locality: unknown. Type host: Myotis myotis (Kolenati, 1856). Material. F, 4 N1 ex Natterer’s bat Myotis nattereri , from Staritsa, 29 February 2020, leg. O.L. Orlov, A.A. Emelyanova; 9 N1 ex Myotis nattereri , N1 ex Myotis mystacinus , 3 N1 ex Myotis brandtii , from Samara, 25 November 2001, leg. D.G. Smirnov; N1 ex M . brandtii , M ex Plecotus auritus , 5 N1 ex M . daubentonii , 4 N1 ex M . dasycneme , from SNR “Samarskaya Luka”, 1-31 May 2005 leg. D.G. Smirnov. Distribution in Russian Federation: Leningrad Province (Stanyukovich, 1990a; Orlova et al ., 2015d), Tver Province (present paper), Samara Province (present paper), Northern Osetiya Republic (Stanyukovich, 1997), Sverdlovsk Province (Orlova, 2011), Chelyabinsk Province (Orlova & Orlov, 2013), Altai Region (Orlova et al ., 2017a), Primorskiy Region (Tiunov et al ., 2021), [Far East] (Stanyukovich, 1997), [Urals, Altai] (Orlova et al ., 2015d). Distribution outside Russian Federation: Europe (Radovsky, 1967), Central Asia (Stanyukovich, 1997). Hosts. Myotis myotis (Radovsky, 1967), M . blythii (Radovsky, 1967), M . brandtii (Orlova, 2011), M . dasycneme (Stanyukovich, 1990a), M . daubentonii (Stanyukovich, 1990a), M . nattereri (Stanyukovich, 1997; present paper), M . brandtii (Stanyukovich, 1990a), M . macrodactylus (present paper), M . mystacinus (Orlova & Orlov, 2013), Vespertilio murinus (Beron, 2014), Plecotus auritus (Orlova & Orlov, 2013), Murina hilgendorfi (as M . leucogaster — Stanyukovich, 1997), Rhinolophus ferrumequinum (Radovsky, 1967), Rh . hipposideros (Radovsky, 1967), ...